If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + 4 + 3c = -16 Reorder the terms: 4 + 2c + 3c = -16 Combine like terms: 2c + 3c = 5c 4 + 5c = -16 Solving 4 + 5c = -16 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5c = -16 + -4 Combine like terms: 4 + -4 = 0 0 + 5c = -16 + -4 5c = -16 + -4 Combine like terms: -16 + -4 = -20 5c = -20 Divide each side by '5'. c = -4 Simplifying c = -4
| 2x^2+1=2x+12 | | 4y-5x=40 | | .6x+1.9x=5 | | .6x+1.9=5 | | 2x^2+43x-2730=0 | | a+5=3 | | 7-6(3-8x)=0 | | x^2-14x+36= | | log(100)=10 | | ?10x+1+7x=37 | | ?10x+1+7x=32 | | ?10x+1+7x= | | ?10x+1+7x=37 | | log(x+5)-log(1-5x)=0 | | .50(x-6)+1=2(x-10)-3 | | 6x+4+8x+18+(180-20x+4)=180 | | 10y-x= | | 3w-10=50 | | log(x+5)=log(1-5x) | | 16n^2-24n+9= | | 4x-(6x-4)= | | 2x-4(x-1)= | | 5x^2-30x+1=0 | | 2x^3-3x^2+x=75 | | y+2=b^3 | | y=27+-7x | | 10x-10+6=2x+8 | | y+1=-7(x-4) | | f(x)=64-x^3 | | x=2.4+0.4X | | 4x+5+2=2 | | 5g+5w=q |